The Potential Role of Value Management in Construction Industry Using Primavera - Subramani, T; Cherian, Joe (International Journal of Engineering and Technology, 2018)
EVM (Earned value management) is a undertaking management tool that uses records primarily based on value, agenda and work performance to outline the modern fame of the project. This facilitates the supervisor to extrapolate current developments to predict their probably very last impact. this approach is proved effective in fee manage. the primavera is project management software program which enables customers to track and analyze performance of task. The document wizard in primavera creates custom designed reviews that extract precise records from its database. The paper outlines the fundamental principles of the EVM & how it could be used effectively for unique challenge with assist of primavera. Additionally a few advantages and headaches of EVM as regards  to Indian creation area. Many construction tasks be afflicted by time and value overruns because of a multiplicity of things. This technique allows everything in evaluation of all budgeted value of work to real value. The existing have a look at deals with the scheduling and venture tracking manner alongside it also discusses principal parameter’s involving in the calculation of earned cost analysis in fee and time control of civil construction project. Using an example of real time venture, methodologies and analysis are demonstrated in this paper.
Keywords: Potential; Role; Value; Management; Construction; Industry and Primavera.